The Kg‐antigen, RhAG with a Lys164Gln mutation, gives rise to haemolytic disease of the newborn. (23rd July 2020) - Tanaka, Mitsunobu; Abe, Takaaki; Minamitani, Takeharu; Akiba, Hiroki; Horikawa, Toshihiro; Tobita, Ryutaro; Isa, Kazumi; Ogasawara, Kenichi; Takahashi, Hideo; Tateyama, Hidemi; Tone, Satomi; Tsumoto, Kouhei; et al.
Summary: The Kg‐antigen was first discovered in an investigation of a mother whose infant had haemolytic disease of the newborn (HDN). The antibody against the Kg‐antigen is believed to be responsible for HDN. The Kg‐antigen is provisionally registered under the number 700045, according to the Red Cell Immunogenetics and Blood Group Terminology. However, the molecular nature of the Kg‐antigen has remained a mystery for over 30 years. In this study, a monoclonal antibody against the Kg‐antigen and the recombinant protein were developed that allowed for the immunoprecipitation analysis. Immunoprecipitants from the propositus' red blood cell ghosts were subjected to mass spectrometry analysis, and DNA sequence analysis of the genes was also performed. A candidate for the Kg‐antigen was molecularly isolated and confirmed to be a determinant of the Kg‐antigen by cell transfection and flow cytometry analyses. The Kg‐antigen and the genetic mutation were then screened for in a Japanese population. The molecular nature of the Kg‐antigen was shown to be RhAG with a Lys164Gln mutation. Kg phenotyping further clarified that 0.22% of the Japanese population studied was positive for the Kg‐antigen. These findings provide important information on the Kg‐antigen, which has been clinically presumed to give rise to HDN.